"Beauty won't boil the pot:" Aesthetic discourse, memory, and urban development in Edinburgh. (26th June 2020) - Ballard Tooley, Christa
Abstract: In 2005, a development proposal for the largest city center redevelopment in Edinburgh, Scotland since the 18 th century was presented to the public. Intended for the medieval and recently industrial part of the city's Old Town, the proposal sparked years of intense argument over appropriate development for the area. Perhaps no aspect of that debate has incited as much rancor as the question of aesthetics. Arguments over development aesthetics, which mobilized a broad spectrum of actors—from corporate leaders, to city councilors, heritage organization members, private architects, city planners, residents and lay observers—were dismissed by the development's supporters as superficial and insignificant. Instead, I argue that this aesthetic transformation pursued by the developer was accurately perceived by many, in particular the area residents, as a means of spatialized forgetting. The industrial history of the area would be eclipsed by the physical transformations pursued in this development, and in response residents asserted a conflicting aesthetic ethic as native to the neighborhood. This article explores the discourse of aesthetics and its impacts upon this development process, concluding that such discourse represents a strategy of dispossession in neoliberalizing urban development.